Transformation of Novel Ronggeng Dukuh Paruk into Film Sang Penari: an Intertextual Analysis - Suaka, I Nyoman (Institut Seni Indonesia Denpasar, 2014)
This present study was intended to identify the transformation of the novel Ronggeng Dukuh Paruk into the film Sang Penari (the Dancer). The novel, which was written by Ahmad Tohari, was adopted into the film which was directed by Ifa Ifansyah. The film was highly appreciated due its highly interesting acting, plot and theme, in which it was narrated that the art tradition of ronggeng was interfered with politics. This present study is a qualitative one with intertextual analysis. The data were collected using documentation and observation methods. The document used was the novel Ronggeng Dukuh Paruk and two CD’s of the film Sang Penari. The observation method was used to view and observe visually the presentation of the film Sang Penari. The film which was presented on one of the private television stations was also watched. This present study analyzed the relation between the text of the novel and the visual text and environmental context of the supporting community of the ronggeng traditional art. The result of the study showed that the transformation of the novel Ronggeng Dukuh Paruk into the film Sang Penari (the Dancer) led to textual transformation such as deconstruction and text appreciation. The textual deconstruction took place as several important scenes in the novel did not appear on the film. The textual appreciation took place as the historical event G 30 S PKI (the Indonesian Communist Movement which took place on 30 September) was added, which the novel did not contain. In the novel, which was edited in 1982, such a bad historical event in Indonesia was not clearly mentioned.